Effect of integrated use of the different types of organic fertilizer application treated with effective microorganisms on the growth and yield of paddy / Noor Liyana Subhi - Subhi, Noor Liyana (Faculty of Plantation and Agrotechnology, 2015)
Study on the effects of different types of organic fertilizer treated with effective microorganisms (EM) on the growth and yield performance of paddy was conducted at field Universiti Teknologi MARA Jasin, Melaka for four months period. The study was carried out by using Variety MR220 CLI of paddy obtain from MADA. Seven different types of organic fertilizer were prepared with treated by 1 :500 EMI (Chicken Dung + EM), (Cow Dung + EM), (Paddy Husk Ash + EM), (Chicken Dung + Paddy Husk Ash + EM), (Chicken Dung + Cow Dung + EM), (Cow Dung + Paddy Husk Ash + EM) and (Chicken Dung + Cow Dung + Paddy Husk Ash + EM). Those treatments were used in this study to determine the most suitable different types of organic fertilizer treated with EM for the paddy crop. The conventional compound fertilizer were used as control treatment. The study was conducted in a Completely Randomized Design (CRD) with eight treatments and four replications. Data on the parameters selected are plant height, number of tillers, number of panicles, weight of rice panicle, 100 grains weight, number of filled grain, weight of filled grain and grain weight,. Results from the ANOVA indicated that there has a significant increase in yield of paddy. Means separation using Tukey's test showed treatment T7 (Chicken Dung + Cow Dung + Paddy Husk Ash + EM) was found to have the most significant effect in the increase in all the parameters (P≤0.05).